Career guidance of vocational school teacher - Santoso, Yulianto (Jurnal Aplikasi IPTEK Indonesia, 2021)
This paper aims to explain the results of research on teacher career guidance conducted by the principal of vocational school. As for the indicators are 1) providing motivation 2) implementing job rotation 3) opportunity to participate in training/upgrading 4) opportunity to continue education. The study population numbered 75 teachers at Sekolah Menengah Kejuruan 3 Padang. Samples were taken using stratified random sampling technique, so that a sample of 54 respondents were obtained. The research instrument used in the form of a questionnaire compiled in the form of a Likert Scale model and tested for validity using the formula of the hierarchical correlation and reliability test using the alpha formula. The index of validity and reliability is significant at 95% confidence level. Analysis of data research using the average formula. The results of data analysis of the research show that the average teacher career guidance by the principal with a score of 3.50, which means that it is in the category quite good. With this it can be concluded that career guidance by the principal is still not optimal yet. So it needs a more effort from the principal so that the teacher's career guidance takes place as expected.